Correlation between Abnormal Signal-Averaged ECG and Left Ventricular Ejection Fraction in Patients of Acute Myocardial Infarction within Seven Days of Sustaining the Infarction. - Malek, Mohammad Abdul; Iqbal, Sayed Asif; Haque, AFM Shamsul; Sultana, Sayeda Aleya; Rahman, Md Waliur; Rahman, Md Mukhlesur (University Heart Journal, 2020)
Objective: This study sought to evaluate the correlation of left ventricular ejection fraction (LVEF) with Signal – Average Electrocardiogram (SAECG) in patient with acute myocardial infarction. Background: Post MI risk stratification is still a debatable issue. Appropriate investigation to ascertain the patient at risk of sudden cardiac death is sometimes difficult. Abnormalities in the SAECG have been determined to be independent predictors of risk of developing ventricular arrhythmias in patients convalescing from myocardial infarction. Correlation of LVEF with SAECG will identify the small group of patient at risk of fatal arrhythmia. Method: This observational study was carried out in the cardiology center, Combined Military Hospital, Dhaka cantonment during the period of January 2010 to January 2011. Patient with first acute myocardial infarction within 7 days of sustaining acute myocardial infarction were included in the study. All three parameters of SAECG (Total QRS duration, Low Amplitude Signal (LAS) under 40μvolt, Root - mean -square (RMS) voltage of last 40 msec) were recorded, and basing on the results, patients were grouped into normal or abnormal SAECG. Result: A total of 106 patients of acute MI were studied. Mean age of the patients were 54(SD±10.5) years (range 34 to 90 years). Only 13(12%) patients were female with male to female ratio of 7.15:1. 32% patients were thrombolysed & abnormal SAECG was more in patients who were thrombolysed (p value<0.05) but logistic regression analysis showed no significant association. Smoking had significant association with abnormal SAECG by univariate analysis (p value<0.05) but logistic regression analysis showed no significant association with smoking and sex (p value >0.05). 46% patients had inferior/inferoposterior myocardial infarction. Abnormal SAECG was more among patients with inferior MI (p <0.05). Mean LVEF was 45.81% (SD±9.68). Correlation of LV function was assessed by both Pearson’s correlation and Ç2 test but no significant association was seen. Logistic regression analysis showed the similar result. Conclusion: In our study, no correlation was found between abnormal signal-averaged ECG and left ventricular ejection fraction following acute myocardial infarction. Further large, multi center study with more selective variables is required to find out any association of SAECG and LV ejection fraction. University Heart Journal Vol. 17, No. 1, Jan 2021; 3-9